Boosting butyrate and hydrogen production in acidogenic fermentation of food waste and sewage sludge mixture: a pilot scale demonstration. (10th June 2023) - Gottardo, Marco; Dosta, Joan; Cavinato, Cristina; Crognale, Simona; Tonanzi, Barbara; Rossetti, Simona; Bolzonella, David; Pavan, Paolo; Valentino, Francesco
Abstract: Within the urban scenario, the application of a biorefinery technology value chain can foster the conversion of different organic substrates into marketable and added-value products. In this work, a pilot-scale dark fermentation (DF) process has been carried out as a key step for volatile fatty acids (VFA) and hydrogen production from the liquid fraction of sewage sludge and food waste mixture. Six operating conditions have been monitored in terms of yield and process stability, by changing the hydraulic retention time (HRT) from 4 to 6 days and applying a short-term hyper-thermophilic hydrolysis (70 °C, 8 h) on the same feedstock mixture. A tubular centrifugation was utilized to remove part of the biosolids (driven to biogas production) before the DF step, which was applied on the soluble and/or colloidal organic matter only. The hydrolysis step favored the following acidification process, in which a fermentation yield up to 0.42 g CODVFA /g VS0 was achieved at 5 days as HRT. Hydrogen production (up to 34.4% v/v and 0.046 m 3 H2 /kg VS0 ) was positively affected by the hydrolysis application and by the decrease of the HRT, highlighting the possibility to produce biohythane in the modeled two-phases anaerobic bioprocess. On the other hand, without the application of the hydrolysis, a selective production of butyric acid (up to 75% COD basin) was achieved, furnishing a different valorization route for the chosen urban organic feedstock. Changes in operating conditions and performances were also reflected by the adaptation of the microbial community, whose characterization highlighted the occurrence of several fermentative microorganisms (e.g., Clostridiaceae, Ruminococcaceae ). Graphical abstract: Image 1 Highlights: Acidification yield increased with hydrolyzed FW and sludge mixture in DF process. Shorter HRT and mild hydrolysis favored specific hydrogen yield and production. Selective butyrate production was obtained with no hydrolyzed feedstock mixture. The microbial community was heavily affected by the hydrolyzation step. Hydrolysis step was necessary to reach H2 content above 10% v/v in the biohythane.